Treatise on hill roads - Gahlowt, R. S.; Gupta, V. P. (Ved Parkash) (Delhi : Standard Book House, 1992)
With reference to India.
Includes index.
Includes bibliographical references (p. [352]).
Keywords: Mountain roads -- India -- Design and construction; Mountain roads -- India -- Maintenance and repair